Impact of Continuous RESET/SET Operations on Endurance Characteristic of Phase Change Memory - WU Lei, CAI Daolin, CHEN Yifeng, LIU Yuanguang, YAN Shuai, LI Yang, YU Li, XIE Li, SONG Zhitang (Shanghai Jiaotong Daxue xuebao, 2021)
In order to explore the effects of continuous RESET operations and continuous SET operations on the endurance characteristic of phase change memory (PCM), the endurance characteristics of PCM at different ratios of RESET-SET times are studied based on a 4Mbit PCM chip. The variation of resistance distributions of PCM after continuous RESET and continuous SET operations are measured. The endurance characteristics of PCM in RESET-only and SET-only operations are compared with the typical endurance characteristic. Besides, the causes and repair methods of failure are also discussed. Moreover, the endurance characteristics of PCM at 8 different RESET-SET ratios are compared. The research results show that continuous RESET operation has little effect on the endurance characteristic of PCM, and the endurance characteristic of PCM in the RESET-only mode is on the same order as the typical endurance characteristic. However, the continuous SET operation has a significantly destructive effect on the endurance characteristic of PCM, and the endurance characteristic of PCM in the SET-only mode is 2 orders of magnitude lower than the typical endurance characteristic. The failure process of PCM caused by continuous RESET operation is irreversible while the failure process of PCM caused by continuous SET operation can be repaired by intermittent RESET operation.